Signet-ring cell/histiocytoid carcinoma of the eyelid: A case report and review of the literature - Jantima Tanboon (2018)
Signet-ring cell/histiocytoid carcinomas of the eyelid are rare, slow-growing, and locally aggressive tumors. They predominantly affect elderly men and clinically resemble chronic inflammatory process such as blepharitis and chalazion. To date, the histogenesis of the tumors is still controversial. Only 27 cases of primary signet-ring cell/histiocytoid carcinomas of the eyelid are published in the literature. Local recurrence and distant metastasis occur in 8 and 7 cases, respectively. We report clinical, radiographic, and pathological features of a case of signet-ring cell/histiocytoid carcinoma of the eyelid with review of relevant literature. Copyright © 2013 by Lippincott Williams & Wilkins.